ETIKA DAN TANTANGAN DAKWAH DI ERA POST TRUTH DAN DISRUPSI - Nurhaidah, Siti Nuri; Hidayat, Rahmat; Ramdani, Riska; Rahman, Deni; Wardi, Miftahussa’adah; Arafah, Mudrikatul; Maskur, Asep (Moderation | Journal of Islamic Studies Review, 2025)
The main characteristic of the post-truth era is the proliferation of fake news (hoaxes), disinformation, and misinformation that spreads at an extraordinary speed. This information is often designed to manipulate emotions, reinforce polarization, or damage reputations. The line between fact and fiction becomes blurred, making it difficult for society to distinguish between what is true and what is not. This phenomenon is exacerbated by the role of social media and algorithms that create echo chambers or filter bubbles. Users tend to be exposed only to information that aligns with their own views, which further reinforces existing beliefs and makes them resistant to contrary information. This creates an environment where confirmation bias is highly dominant. In the context of preaching, the post-truth era presents a significant challenge. Straightforward preaching messages based on strong evidence can easily be distorted or attacked by narratives based on emotions and slander. The community is also affected. highly at risk of exposure to deviant teachings because it is difficult to distinguish credible sources of information. The impact of this era is not limited to information but also affects public trust in institutions—including religious organizations and scholars. When facts are questioned and emotions dominate, the authority of scientific and religious knowledge can erode, which in turn can threaten social and religious stability.